Get backed, get big, get bought : plan your start-up with the end in mind - Barrow, Colin (Capstone, 2009)
"If your main ambition is to make big money from your business, you're already on the right track. Over 4 million people start up businesses in the UK each year but only 1% become millionaires. Start with the end in mind and you could be one of them. Colin Barrow, bestselling start-up author and business investment specialist, shows you how to shape up for a sale right from the world go. With practical advice, tools and stories from those who have done it, you'll find out how to guide your start-up business towards the payday of your dreams"--Resource description page